2022
DOI: 10.30862/jri.v2i2.92
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing information and communication technology applications in chemistry learning

Abstract: Information and communication technology (ICT) is crucial to the educational growth of any country and the academic interactions and collaborations of students. The study determined the extent of ICT application in chemistry instruction in Anambra State, Nigeria, secondary schools. This study uses a descriptive survey. A total of 133 students and 12 chemistry teachers as samples. The t-test was used to test the research hypothesis. The study's findings revealed a low extent of ICT application in teaching and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Issues such as technological inequality and the need for comprehensive teacher training stand in the way of full integration. Despite these challenges, the continued development and adaptation of ChatGPT in educational institutions promises a more engaging and effective learning environment for students and paves the way for an innovation in chemistry education [12]. In the most of studies, the attitudes of students towards artificial intelligence distributes from enthusiastic to indifferent and cautious.…”
Section: Figure 1 -The Chronology Of the Integration Of Digital Techn...mentioning
confidence: 99%
“…Issues such as technological inequality and the need for comprehensive teacher training stand in the way of full integration. Despite these challenges, the continued development and adaptation of ChatGPT in educational institutions promises a more engaging and effective learning environment for students and paves the way for an innovation in chemistry education [12]. In the most of studies, the attitudes of students towards artificial intelligence distributes from enthusiastic to indifferent and cautious.…”
Section: Figure 1 -The Chronology Of the Integration Of Digital Techn...mentioning
confidence: 99%
“…In the teaching and learning process of basic chemistry concepts, it is important to consider not only the importance of managing and understanding the table and periodic properties, but also the significant difficulties associated with memorising these concepts, which often lead to confusion and fundamental conceptual gaps. Recently, numerous activities have been described in the literature to improve the teaching and learning process in the field of chemistry [14,17]. Specifically, with regard to the content and properties of the periodic table, many teachers and researchers have developed and incorporated activities that facilitate students' learning of these concepts [1,3,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, other researchers revealed that nearly 40% of students have experienced text anxieties. [14,15] Among chemistry students, Nwafor et al [16] posited that more than 50% of chemistry students in Nigeria are confronted with anxiety prior to and during test circumstances that frequently affects their achievements. This presents a concern and calls for remediation.…”
Section: Introductionmentioning
confidence: 99%